2011
DOI: 10.1080/11250003.2010.487075
|View full text |Cite
|
Sign up to set email alerts
|

Histological stages of retinal morphogenesis in chicken – a descriptive laboratory research

Abstract: The similarity of the developmental anatomy of chicken with that of mammals has rendered it an appropriate animal model for understanding the anatomical and pathological aspects of human biological systems. The present study describes the age-dependent morphological differentiation stages of developing retina of chick embryos. The retinae of chicken embryos of ages 10 and 15 days incubation, of newly hatched chicks and also that of adult chicken were studied histologically. The retinae were processed both for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…These retinal layers appeared clearly in all developmental stages except the OPL, which was not observed in eight-day chick embryos but was observed at the other developmental stages. This is consistent with the results of previous studies [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These retinal layers appeared clearly in all developmental stages except the OPL, which was not observed in eight-day chick embryos but was observed at the other developmental stages. This is consistent with the results of previous studies [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…The retinae of chicken embryos (E8 and E15), newly hatched chicks (P2), and adult chickens (P50) were studied histologically. Our observations of the morphological stages of the retinal layers using H&E staining were consistent with those of previous studies [ 3 , 15 ]. All retinal layers were clearly visible and ordered as follows: the NFL, GCL, IPL, INL, OPL, ONL, and RPE.…”
Section: Discussionsupporting
confidence: 93%
“…Kujawa-Hadryś et al [ 101 ] reported that the thickness of the corneal epithelium increased markedly through the end of incubation in chick embryos. Several studies have been conducted examining normal retinal structure in poultry [ 102 , 103 ]. However, there is insufficient information about the effects of MSG on the cornea and retina in chicken embryos.…”
Section: Discussionmentioning
confidence: 99%
“…These areas are at high risk [7]. The reason why malaria emerged and spread is so fast in Pakistan is because of the Afghan refugees who migrated during Soviet War to Pakistan and especially to KP, they didn't have enough facilities and hence they were living in camps, they couldn't use nets for their prevention from the mosquitoes as a result they were prone to the parasite and later 150,000 cases were reported in refugees and the malarial parasite started to appear in the people of Pakistan [8].…”
mentioning
confidence: 99%